Does tax enforcement disparately affect domestic versus multinational corporations around the world? - De Simone, Lisa; Stomberg, Bridget; Williams, Brian (Contemporary Accounting Research, 2023)
Abstract Global tax enforcement policies have received increased attention since the financial crisis, with much stated focus on curbing perceived harmful tax practices of multinational corporations. Yet there is a dearth of evidence on possible differential effects of home‐country tax enforcement on multinationals. We take a step toward filling this void in the tax policy discussion by examining whether there is a differential relation between changes in home‐country enforcement and the tax avoidance of domestic versus multinational corporations. Using OECD data on 50 countries from 2005 to 2019, we find increases in home‐country enforcement are associated with lower levels of tax avoidance for domestic firms than for multinational corporations. Using a subset of firms from the Bureau van Dijk database, we find that multinationals avoid more tax in foreign countries when home‐country enforcement increases. Results are stronger for multinationals with a higher proportion of subsidiaries in low‐tax countries and when enforcement spending is low. These findings have implications for policy‐makers and highlight the importance of coordinated enforcement efforts across jurisdictions—such as the recently proposed global minimum tax—to successfully curb multinationals' worldwide tax avoidance.